Research on Doping in Sport (2001)
Berichtsband des Workshops "Research on Doping in Sport", der 2001 an der Universität Oslo stattfand. Dokumentuiert sind folgende Beiträge: Sportive Nationalism and Doping (John Hoberman, University of Texas, USA) Doping in sport: a medical sociological perspective (Ivan Waddington, University of Leicester, UK) Sport policy and doping: a research agenda (Barrie Houlihan, Loughborough University, UK) Coping with Doping: Sport associations under organizational stress (Karl-Heinrich Bette, GER)